Optimal Search Auctions - Jacques Crémer; Yossi Spiegel; Charles Zhoucheng Zheng (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
We study the design of profit maximizing single unit auctions under the assumption that the seller needs to incur costs to contact prospective bidders and inform them about the auction. With independent bidders' types and possibly interdependent valuations, the seller's problem can be reduced to a search problem in which the surplus is measured in terms of virtual utilities minus search costs. Compared to the socially efficient mechanism, the optimal mechanism features fewer participants, longer search conditional on the same set of participants, and inefficient sequence of entry.
Keywords: 330; Auktionstheorie; Suchtheorie; Theorie